Sumbangan Tradisi Barat dan Islam Terhadap Idea Masyarakat Sivil: Contributions of Western and Islamic Traditions to the Idea of Civil Society - Tumin, Makmor; Che Soh, Mazlan (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
The concept of civil society today is strongly influenced by the idea of liberalism which values individual freedom and autonomy. The main takeaway from this idea is that the role of the state, religion, and family must be minimized to ensure that the freedom and rights of individuals are achieved. Nevertheless, problems such as global warming and moral collapse indicate that without the role of nation, religion, and family, such problems would not be able to be curbed properly. The objective of this article is to highlight these three aspects from the perspectives of two traditions of thinking on the concept of civil society, namely the Western tradition and Islamic tradition. The method used is discourse analysis based on secondary data to understand the intellectualism and dynamism of these two traditional lines. This article emphasizes that the concept of Western civil society, which is deeply obsessed with anti-state approaches and intermediaries separating the role of religion, must be revisited. Accordingly, the role of the state, religion, and family in the concept of civil society needs to be reconstructed.